Mazagaon Masjid - Mumbai Archive Project Team (Jio Institute, 2024)
The entrance to the Mazagaon Masjid, established in 1890. Islam came to Mumbai through traders, saints, and preachers who arrived from various parts of the Indian subcontinent, and even from foreign lands. Trade, business, and commerce were dominated by the Bohras, the Khojas, and the Kutchi Memons. As a result of this mixed heritage, the Muslim population in Mazagon is diverse, with various sects having built mosques, maqbaras, and dargahs in the area.